2020
DOI: 10.1080/13596748.2020.1802946
|View full text |Cite
|
Sign up to set email alerts
|

Exploring perceptions of the transition from health science practitioner to academic

Abstract: Transitioning from a clinical practitioner to an educator in the health sciences is a difficult task for many professionals. Although, clinically, these individuals have achieved a level of expertise, they are not necessarily trained to teach in a classroom setting and may find it difficult to transition into their role as novice. The purpose of this qualitative case study was to examine faculty members' preparedness during their transition to academia and their perceptions of the need for more support during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…While minority PA participants were willing to leave clinical practice and assume new roles as PA educators, they lacked pedagogical training, which is crucial in educating future PA clinicians effectively. 32 Both this study and current literature highlight the lack of mentoring and professional development opportunities pertinent to PA education. PA faculty participants reported that mentoring experiences were primarily informal and mainly provided by peers within their programs or through networking with minority PA faculty outside of their institutions.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…While minority PA participants were willing to leave clinical practice and assume new roles as PA educators, they lacked pedagogical training, which is crucial in educating future PA clinicians effectively. 32 Both this study and current literature highlight the lack of mentoring and professional development opportunities pertinent to PA education. PA faculty participants reported that mentoring experiences were primarily informal and mainly provided by peers within their programs or through networking with minority PA faculty outside of their institutions.…”
Section: Discussionmentioning
confidence: 79%
“…Teaching in the health science professions requires a high skill level to meet teaching standards. 32 As participants discussed their preparation experience, all reported that they had received no training in the form of mentoring or professional development. This is consistent with findings from PAEA 33 reporting that 70% of new PA faculty who transition from clinical practice to academia lack formal pedagogical training.…”
Section: Discussionmentioning
confidence: 99%
“…Harland et al (2014) and Matsumoto (2016) identified the importance of the individual sense of identity and how this can positively link to transformation in teaching practices. Newer teachers also reported imposter syndrome linked to identity as an academic (Stewart, 2019). However, belonging and a sense of community, or group identity, appears to be equally, if not more influential in navigating trouble and liminality.…”
Section: Literature Reviewmentioning
confidence: 97%
“…This appeared to be aggravated by the contrast with teachers' 'home' disciplines, where their sense of being expert contrasted with feelings of being a novice when learning about pedagogy (Marquis et al, 2017;Webb, 2015). For Stewart (2019) tension between subject knowledge and confidence in delivering teaching was also manifested in clinicians transitioning into academic posts. This trouble and liminality linked not just to personal comparisons between disciplinary expertise and learning about learning and pedagogy but also to views of disciplinary colleagues, who did not always appear to value the study of learning and teaching (Flavell et al, 2019;Manarin & Abrahamson, 2016;Warhurst, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation